Localizing western expertise: İhsan Dogramaci, S. Rasithatipoglu, and the quest for scientific developmentin modern Turkey - ERKEN, ALİ (My University, 2022)
This article discusses the dynamics between Western experts and local technocrats in Turkey in their quest for scientific development in the first decades of modern Turkey. Based on primary archival sources, it examines the work of Ihsan Dogramaci (d. 2010) and S. Rasit Hatipoglu (d. 1973), who led various projects in the fields of medical and agricultural development. Ihsan Dogramaci, a prominent scholar in the medical sciences, established a close partnership with the Rockefeller Foundation in the 1950s and led the establishment of Hacettepe University in the 1960s. S. Rasit Hatipoglu was an agricultural expert who worked closely with German scientists, was involved in developing the Higher Institute of Agriculture in Ankara in the 1930s and then served as minister of agriculture in the 1940s. The article notes that the transfer of Western science and institution-building required the appropriation of local knowledge, political and intellectual networks and a negotiation process that included global and national challenges.
Keywords: Sosyal ve Beşeri Bilimler; Felsefe; Bilim Tarihi; Sosyoloji; Social Sciences and Humanities; Philosophy; History of Science; Sociology; BİLİM TARİHİ VE FELSEFESİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); HISTORY & PHILOSOPHY OF SCIENCE; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Bilim Tarihi ve Felsefesi; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; History and Philosophy of Science; Social Sciences & Humanities; history of medical sciences; history of development; history of agricultural sciences; history of Turkey